Perencanaan Peningkatan Kualitas Produk Raket dengan Metode Quality Function Deployment - Lukman, Moh. (Jurnal Teknik Industri, 2009)
Small Industry Abadi location in central small industry raket Sukun-Malang, so many kinds racket product are many variables as, racket quality, raket colors, rakets price, will give the customer many choice product rackets. Demand racket products are fluctuative from periods to another periods because there are factors: school holiday, and badminton championship in scale national cup and world cup as All England so demand will be increase. In central small industry raket thre are many small industry racket, so competition raket product increase,so there are the price will be cheap and quality may be too lower. This competition cause qoitition in raket "X" is low. Antisipacition to win competition we will design good quality raket product fit with attribute racket customers, with methode Quality Function Deployment (QFD). From result of analysis can know that attribute obtaining especial priority to customer is among others chicken eye of strong plastic type and handle of racket is not breakable, besides technical respon which made account of by company is among others wrap handle of sponge cloth and of racket don't use extension T. Besides got by price for new desain equal to Rp19.300,- at the price of selling Rp22.500,- got by cheaper price of Rp1.300,- compared to old desain racket that is equal to Rp20.600,- at the price of selling Rp25.000.